A kaleidoscopic circumspection of development planning. With contextual reference to Nepal - Beenhakker, A. ([Rotterdam]: Rotterdam University Press, 1973)
The book is a case study in applied and theoretical programming, as part of a process of transformation. The case was adopted in a country which is fascinating not for its mountains alone.
Bibliography: p. 166-167.
osa; 29/06/18
Loans
Keywords: Economic History; Nepal; Developing countries